The Presentation of Eating Disorders in Saudi Arabia - Jawed, Aisha; Harrison, Amy; Dimitriou, Dagmara (Frontiers in Psychology, 2020)
Objective: There is lack of information on the presentation of eating disorders (EDs) in Saudi Arabia using gold standard clinical tools. The present study aimed to provide data on the presentation of EDs in Saudi Arabia using clinically validated measures. Method: 133 individuals (33 male) with a mean age of 22 years (2.63) completed three measures: the Eating Disorder Examination, a semi-structured interview, the Eating Disorder Examination Questionnaire, a self-report measure, and the Depression Anxiety and Stress Scale to measure comorbid symptoms. Results: Individuals in Saudi Arabia reported higher levels of restraint, eating concern and shape concern and a higher global score, but lower levels of weight concern on the EDE-Q compared to the EDE. Female participants reported a higher global score, alongside significantly higher scores on the restraint, shape concern and weight concern subscales than males. The most common ED subtype was other specific feeding or ED. Compared with Western community samples, symptom severity in this purposive sample obtained from community settings was significantly higher in this sample. Discussion: Individuals with eating, weight and shape concerns in Saudi Arabia may feel more comfortable expressing their symptoms on a self-report tool compared with a face to face interview. However, it is possible that a self-report measure may over-estimate the severity of symptoms. The data suggest that clinicians in Saudi Arabia should regularly screen for EDs in all genders. It is also important to note that ED symptoms are a cause for concern in young people in Saudi Arabia.